Performance analysis of maximum ratio transmission based FSO link over Malaga turbulence channel - Ibrahim, Abdulgani A.; Gucluoglu, Tansal (ELSEVIER, 2019)
Free space optical (FSO) communication systems are becoming popular since they can provide high data rates over license-free spectrum. However, the performance of FSO communication links deteriorate due to atmospheric turbulence effects. In this paper, we present the performance improvement of FSO links by employing maximum ratio transmission (MRT) technique. Atmospheric turbulence effects are considered to follow the generalized Malaga (M) distribution. Exact and asymptotic mathematical expressions for both bit error rate and outage probability performances are derived and then diversity gain of the system is obtained. Theoretical findings are verified with Monte-Carlo simulations. Our results show that increasing the number of transmitting apertures can effectively mitigate the deteriorating effects of the atmospheric turbulence.
Keywords: Free space optical links; Atmospheric turbulence; Maximum ratio transmission; Bit error rate; Outage probability; SPACE OPTICAL LINKS; POINTING ERRORS; TIME DIVERSITY; COMMUNICATION; SYSTEMS; MODEL; PROBABILITY; Optics